Methanolic Moringa oleifera leaf extract protects against epithelial barrier damage and enteric bacterial translocation in intestinal I/R: Possible role of caspase 3 - Afolabi, O A.; Akhigbe, T M.; Akhigbe, R E.; Alabi, B A.; Gbolagun, O T.; Taiwo, M E.; Fakeye, O O.; Yusuf, E O. (Frontiers in Pharmacology, 2022)
Activation of caspase 3 has been implicated in the pathogenesis of I/R injury in various organs, but there is a paucity of data on its role in IIRI. Also, no reports were found on the beneficial role of methanolic Moringa oleifera leaf extract (MMOLE) in IIRI. This study investigated the role of caspase 3 in IIRI, and the impact of MMOLE in IIRI. Male Wistar rats were randomized into five groups; the sham-operated group that was sham-operated and received 0.5 mL of distilled water for seven days prior to sham surgery, and the IIRI, febuxostat (FEB) +IIRI, low dose MMOLE (LDMO)+IIRI, and high dose MMOLE (HDMO)+IIRI groups that underwent I/R and also received 0.5 mL of distilled water, 10 mg/kg of febuxostat, 200 mg/kg of MMOLE, and 400 mg/kg of MMOLE respectively for seven days prior to I/R. MMOLE alleviated IIRI-induced rise in intestinal and hepatic injury markers, malondialdehyde, TNF-α, IL-6, and myeloperoxidase activities. MMOLE improved IIRI-induced suppression of reduced glutathione, thiol and non-thiol proteins, and superoxide dismutase, catalase and glutathione peroxidase activities. These were associated with suppression of IIRI-induced bacterial translocation and caspase 3. Histopathological findings corroborated with the observed biochemical changes. MMOLE militated against intestinal and hepatic injuries, epithelial mucosal barrier dysfunction, and enteric bacterial translocation associated with IIRI by downregulating oxidative stress-mediated activation of caspase 3. The beneficial effects of MMOLE may be attributed to the antioxidant and antibacterial actions of its constituent bioactive molecules, especially hydrazine, 9-octadecenoic acid, 1,3-dioxolane, oleic acid, and nonadecanoic acid.